CO2 Capture for Dry Reforming of Natural Gas: Performance and Process Modeling of Calcium Carbonate Looping Using Acid Based CaCO3 Sorbent - Zubir, Muhammad Afiq; Afandi, Nurfanizan; Manap, Abreeza; Hamid, Awaluddin Abdul; Ayodele, Bamidele Victor; Liu, Wen; Abd Hamid, Mohd Kamaruddin (Frontiers in Energy Research, 2021)
Several industrial activities often result in the emissions of greenhouse gases such as carbon dioxide and methane (a principal component of natural gas). In order to mitigate the effects of these greenhouse gases, CO2 can be captured, stored and utilised for the dry reforming of methane. Various CO2 capture techniques have been investigated in the past decades. This study investigated the performance and process modelling of CO2 capture through calcium carbonate looping (CCL) using local (Malaysia) limestone as the sorbent. The original limestone was compared with two types of oxalic acid-treated limestone, with and without aluminum oxide (Al2O3) as supporting material. The comparison was in terms of CO2 uptake capacity and performance in a fluidized bed reactor system. From the results, it was shown that the oxalic acid-treated limestone without Al2O3 had the largest surface area, highest CO2 uptake capacity and highest mass attrition resistance, compared with other sorbents. The sorbent kinetic study was used to design, using an Aspen Plus simulator, a CCL process that was integrated with a 700 MWe coal-fired power plant from Malaysia. The findings showed that, with added capital and operation costs due to the CCL process, the specific CO2 emission of the existing plant was significantly reduced from 909 kg/MWh to 99.7 kg/MWh.